Is Poverty the Root of All Crime? Rethinking Criminality Amid Institutional Failure in Madagascar - Manitra, Ramalina Ranaivo Mikea (Jurnal Kriminologi Indonesia, 2025)
Madagascar continues to grapple with high levels of poverty and weak institutional capacity, creating conditions conducive to widespread and persistent criminality. This paper aims to examine how structural poverty, institutional failure, and state fragility interact to shape patterns of crime through the lens of criminological theories such as strain theory, social disorganisation, and state-centred criminology. Using a qualitative methodology based on a comprehensive literature review of empirical studies, policy documents, and international reports, the paper explores the socio-economic and institutional dynamics underpinning crime in Madagascar. The findings reveal that poverty-driven crime often arises as a rational response to unmet needs, exacerbated by weak governance, corruption, and fragmented social protections. Moreover, informal criminality in some contexts becomes a semi-legitimate form of survival and social organisation. The study concludes by drawing on successful poverty alleviation, social welfare, and governance models from other countries to propose tailored, integrated strategies for Madagascar aimed at reducing crime through comprehensive socio-economic and institutional reforms.